Complexity of unmet basic needs of children in adversity in China's fragmented child protection system - Risk and protective factors from a bioecological perspective - Ning Zhu; Ruoran Qiu; Timo Toikko (Child Protection and Practice)
Background: Child protection system is continually redefined to cover more adversities because studies have identified increasingly more new adversities. The system's focus also extends to “unmet needs”. Objective: This study uses an innovative assessment framework to analyze the unmet basic needs (survival, protection, participation, and development) of children in adversity. Exploring risk and protective factors affecting their total needs at the individual, family, and society levels based on bioecological theory. Participants: The study analyzed data from 1243 children in adversity and their families, covering diverse schooling levels, types of adversity, guardianship arrangements, and family structures, with children aged 6–18 years. Methods: The sample was selected by cluster and systematic sampling. Trained social workers collected door-to-door questionnaire data on demographics, children's basic needs, parental and carer characteristics, and family functioning and environment. Predictors of children's total needs were analyzed using hierarchical linear regression. Results: Children in adversity had higher developmental and participation needs than survival and protection needs. Lower total needs were associated with higher children's strength characteristics and support from relatives or friends. Conversely, family trauma, caregiver negative characteristics, socio-economic resources (debt and housing instability), family dysfunction (intergenerational care difficulties) increased children's basic total needs. Conclusions: Lack of parental awareness and capacity, family stress, and inadequate family support make it difficult for families to meet children's basic needs. Policymakers should acknowledge the negative impact of fragmented child protection systems on child development. An integrated protection system and social services are needed to support families, and improve children's well-being.